Care coordination for chronically ill patients: Identifying coordination activities and interdependencies. (October 2019) - Kianfar, Sarah; Carayon, Pascale; Hundt, Ann Schoofs; Hoonakker, Peter
Abstract: Care coordination is important for chronically ill patients who need assistance from a variety of healthcare professionals especially when they transition through different care settings. There has not been a clear definition of care coordination and its associated activities. This paper provides a two-dimension framework of care coordination for chronically ill patients: 1) coordination activities (i.e. communication and monitoring) and 2) interdependencies (i.e. flow, shared resources, simultaneity). We used this framework in a qualitative content analysis of 12 interviews with healthcare professionals involved in coordinating care of chronically ill patients. We identified a total of 258 care coordination activities and developed categories and sub-categories using the constant comparative method. The first category of care coordination activities involves communication with flow or shared resources interdependencies or both. This category includes arranging services and equipment for the patient, exchanging information about patient transition to different care settings, reporting errors and resolving them, and helping the patient with appointments and transportation. The second category involves monitoring, sometimes combined with communication, with flow or shared resources interdependencies or both. This category includes reviewing medications and services and detecting errors, reviewing patient symptoms and following up if needed, and scheduling follow-up to review patient status. The last category involves communication with simultaneity interdependency. This category involves talking in the same location and developing a plan of care, people exchanging information at the same time, and scheduling delivery of medications/services to correspond with patient arrival home. Finally, we identified characteristics of health information technology that can support these various care coordination activities. Highlights: Coordination has two dimensions: activities and interdependencies. Interdependencies distinguish coordination from cooperation and similar concepts. Coordination activities mainly involve communication, and sometimes monitoring. Types of interdependencies include flow, simultaneity, and shared resources. Most of coordination activities involve shared resource or flow or both.